LIFE-CYCLIC SYSTEM OF ORGANIZING AND MANAGING MASS SPORTS THROUGH AN INTEGRATED TECHNOLOGICAL PLATFORM - AXMATOV M.S. («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
This article considers the concept of lifecyclic system as a promising approach to the organisation and management of mass sports and recreational process on a national scale. Organisational and managerial principles and mechanisms of functioning of an integral life-cyclic continuous system are proposed, as well as the sequence of continuous involvement of its elements - social groups of the population.